2020
DOI: 10.1038/s41598-020-71016-8
|View full text |Cite
|
Sign up to set email alerts
|

How memory effects, check dams, and channel geometry control erosion and deposition by debris flows

Abstract: Debris flows can grow greatly in size and hazardous potential by eroding bed and bank material, but effective hazard assessment and mitigation is currently hampered by limited understanding of erosion and deposition dynamics. We have collected high-resolution pre- and post-flow topography for 6 debris flows over a 3 km long unconsolidated reach of the Illgraben channel in the Swiss Alps with drone-based photogrammetry. We show that the spatio-temporal patterns of erosion and deposition in debris-flow torrents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 50 publications
1
53
0
Order By: Relevance
“…However, changes in ξ are likely only significant when erosion exposes bedrock (Kean et al., 2015), which is not the case on Illgraben's debris fan in the Rhone valley. Moreover, at Illgraben, changes in ξ concentrate near check dams (de Haas et al., 2020), such that spatial variations in ξ tend to cancel each other out leaving ξ unchanged between events. We observe an empirical relationship between ξ and distance r, which evolves over time depending on the flow front velocity (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, changes in ξ are likely only significant when erosion exposes bedrock (Kean et al., 2015), which is not the case on Illgraben's debris fan in the Rhone valley. Moreover, at Illgraben, changes in ξ concentrate near check dams (de Haas et al., 2020), such that spatial variations in ξ tend to cancel each other out leaving ξ unchanged between events. We observe an empirical relationship between ξ and distance r, which evolves over time depending on the flow front velocity (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…This also marks the confluence of the Illgraben channel and a steep lateral slope to the east of it, called Sagenschleif (Figure 1d). In recent years, Sagenschleif has produced mass wasting events, including minor debris flows, providing sediments to the Illgraben channel (de Haas et al., 2020). Entrainment of these sediments can increase the debris‐flow volume and impact forces during runout events in the main canyon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The debris-flow force plate is situated just before the confluence of the Illbach with the Rhône river under the bridge of the main road. This location is relatively far from the debris-flow initiation area (∼5 km) and erosion and deposition along the channel on the fan has been observed (Berger et al, 2011a;de Haas et al, 2020;Schürch et al, 2011). We assume this erosion-deposition effect to be negligible compared to total debris-flow volumes and over longer time scales (years) because the channel is stabilized by many check dams.…”
Section: Debris-flow Observations and Landslide Inventorymentioning
confidence: 98%
“…Tichavský et al 20 found that dry spells and extreme precipitation were the main triggers of landslides in the Outer Western Carpathians of Central Europe, and Stoffel et al 21 found that small rockfalls near Monte Fitz Roy in Argentina, could be triggered by earthquakes of moderate intensity, at large distances from their epicenter. De Haas et al 22 identified a memory effect whereby erosion was stronger at locations where there had previously been strong deposition from debris flows. Erosion did not increase with debris-flow magnitude due to a limit of debris-flow bulking set by channel geometry.…”
mentioning
confidence: 99%